Edge Structural Stability and Kinetics of Graphene Chemical Vapor Deposition Growth - Shu, Haibo; Chen, Xiaoshuang; Tao, Xiaoming; Ding, Feng (ACS nano, 2012)
The energetics and growth kinetics of graphene edges during CVD growth on Cu(111) and other catalyst surfaces are explored by density functional theory (DFT) calculations. Different from graphene edges in vacuum, the reconstructions of both armchair (AC) and zigzag (ZZ) edges are energetically less stable because of the passivation of the edges by the catalytic surface. Furthermore, we predicated that, on the most used Cu(111) catalytic surface, each AC-like site on the edge is intended to be passivated by a Cu atom. Such an unexpected passivation significantly lowers the barrier of incorporating carbon atoms onto the graphene edge from 2.5 to 0.8 eV and therefore results in a very fast growth of the AC edge. These theoretical results are successfully applied to explain the broad experimental observations that the ZZ egde is the dominating edge type of growing graphene islands on a Cu surface.